Taxes and Gender Equality: The Incidence of the 'Tampon Tax' - Thiess Büttner; Frank Hechtner; Boryana Madzharova (Center for Economic Studies and ifo Institute (CESifo), 2023)
Many countries are currently debating whether to reduce or eliminate taxes on feminine hygiene products as a measure to address "period poverty" and promote gender equality. Legislators often reject proposals involving reforms of "tampon taxes" as the pass-through of sales taxes into consumer prices cannot be guaranteed. This paper uses a permanent reduction of the tax on tampons & pads in Germany in 2020 as a natural experiment to study the price and unit-sales effects of the tax. Exploiting an extensive data set on the unit sales and scanner prices of feminine hygiene products in Germany and Italy, our results indicate that the incidence of tampon taxes is fully on consumers, while demand for these products is price-inelastic. We do not find cross-price effects for a closely related product group, which remained taxed at the standard tax rate. Both the pass-through and demand effects are found to be homogenous along the pre-reform market-share and price distributions.
Keywords: H22; H23; I38; J16; 330; tax incidence; pass-through; gender equality; feminine hygiene products; period poverty